Empowering Diversity: A Study Connecting Women in Leadership to Company Performance in the Canadian Music Industry - Women In Music Canada (Women In Music Canada, 2019)
Gender diversity in the music industry is low, both in Canada and internationally. The lack of diversity may represent a competitive disadvantage, as diversity is known to promote innovation and broad thinking, which is precisely what the music industry needs as it undergoes rapid change. This study, performed by Women in Music Canada in collaboration with PwC, assesses the impact of gender diversity of leadership within the Canadian music industry and the impact on company performance.